Diseño de una propuesta metodológica que facilite la detección temprana de alteraciones en extremidades inferiores asociadas a lesiones en el miembro contralateral mediante el uso de imágenes infrarrojas (2018)
The human body carries out thermal regulation processes, allowing to preserve a relatively constant environment in the body before a change in temperature, whether it be a few degrees, from the moment after a shower, high-intensity sports training to inflammatory or infectious processes ; the last corresponding to a metabolic alteration. The organism reacts to the presence of lesions or alterations in tissues through the inflammatory process, so that it is ruled that it corresponds to an inflammation should be characterized by the presence of blush, tumor, heat, pain and functional impotence. The increase in temperature in the affected area, associated with the metabolic activity of restoration of damaged tissue, allows its uptake by means of infrared thermography. The thermal information of a subject can be captured by means of a thermographic camera, since it is a simple, non-invasive, low-cost method, does not generate radiation and allows, through a standardized protocol, to guarantee repeatability of the results. In this document we propose the requirement of a methodological proposal that facilitates the capture, processing and analysis of thermographic information of a subject that presents thermal alterations in the lower extremities associated with a lesion in a contralateral limb. For this purpose, the thermal regulation processes in the human body were investigated, justifying the use of a thermographic camera to detect alterations. In addition, a protocol was elaborated with the purpose of standardizing the capture and processing of the images and thermographic information obtained; The capacity of the protocol was evaluated by means of its implementation with two subjects with fractures in the lower extremities who provided their clinical and lesional history. The use of infrared thermography to detect alterations is validated with the physiology of tissue inflammation, taking into account that the increase in temperature is directly related to the inflammation of the same. The thermal radiation emitted by the subject is captured by the thermographic camera and, under an environment, intrinsic and extrinsic parameters controlled by means of a methodology, the thermographic information obtained over time can be compared, guaranteeing a follow-up to the subject's rehabilitation process